Adobe Photoshop Elements 3.0: Photographers' Guide - Busch, David D. (Thomson Course Technology, 2011)
Which effects are best achieved with a film or digital camera? Which effects are best applied in an image editor? "Adobe Photoshop Elements 3.0: Photographers' Guide" answers these questions and more! It cuts right to the heart of the most misunderstood-but easily applied-tools in Photoshop Elements 3.0, examining each from a photographer's perspective. This unique guide is filled with surprisingly effective examples, simple to follow techniques, and tricks that serve as a jumping-off point to spark your own creativity into action. You don't need to be an ace photographer or image editing expert. This straight-forward book contains everything you need to use Photoshop Elements 3.0 to enhance your images with the kinds of effects you admire.